2016
DOI: 10.1136/annrheumdis-2016-209157
|View full text |Cite
|
Sign up to set email alerts
|

Combined role of vitamin D status and CYP24A1 in the transition to systemic lupus erythematosus

Abstract: Objective We examined whether measures of vitamin D were associated with transitioning to systemic lupus erythematosus (SLE) in individuals at risk for SLE. Methods 436 individuals who reported having a relative with SLE but who did not have SLE themselves were evaluated at baseline and again an average of 6.3 (± 3.9) years later. Fifty-six individuals transitioned to SLE (≥4 cumulative ACR criteria). 25-hydroxyvitamin D (25[OH]D) levels were measured by ELISA. Six single nucleotide polymorphisms (SNPs) in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 62 publications
0
32
1
Order By: Relevance
“…The epidemiological data suggest a possible scenario where greater VDR activity for a given amount of 1,25(OH) 2 D could provide protection in situations of low 25(OH)D. For example, the BsmI BB genotype was associated with type 1 diabetes risk only in environments of high 25(OH)D levels (34). In another autoimmune disease, systemic lupus erythematosus, CYP24A1 rs4809959 modified the effect of 25(OH)D, where for each additional minor allele, increased 25(OH)D was associated with further decreased systemic lupus erythematosus risk (35). Low 25(OH)D concentration was associated with a composite outcome of incident hip fracture, myocardial infarction, cancer, and mortality only in those who had one or more minor allele at VDR loci (36).…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological data suggest a possible scenario where greater VDR activity for a given amount of 1,25(OH) 2 D could provide protection in situations of low 25(OH)D. For example, the BsmI BB genotype was associated with type 1 diabetes risk only in environments of high 25(OH)D levels (34). In another autoimmune disease, systemic lupus erythematosus, CYP24A1 rs4809959 modified the effect of 25(OH)D, where for each additional minor allele, increased 25(OH)D was associated with further decreased systemic lupus erythematosus risk (35). Low 25(OH)D concentration was associated with a composite outcome of incident hip fracture, myocardial infarction, cancer, and mortality only in those who had one or more minor allele at VDR loci (36).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, systemic inflammation, obesity, and parathyroid hormone levels have been associated with changes in circulating vitamin D levels. (12,(35)(36)(37)(38)(39)(40).…”
Section: Effect Of Storage Time and Seasonal Variation On Circulatingmentioning
confidence: 99%
“…Additionally, it is conceivable that symptoms such as fatigue and polyarthralgia may limit the outdoor activity of SLE patient impacting on the UV exposure and vitamin D metabolism. However, a recent study by Shoenfield et al analysing CYP24A1 polymorphisms showed that the photosensitivity and the sun exposure behaviour did not correlate with vitamin D levels, suggesting that the genetic background is a stronger driver of vitamin D status [49,50]. Renal involvement typical of SLE may also affect the vitamin D metabolism by impairing its 1-hydroxylation occurring in kidneys.…”
Section: Risk Factors For Vitamin D Deficiencymentioning
confidence: 99%
“…Genetic variations also participate in regulating the absorption and metabolism of 25(OH)D3 [54]. For instance, intronic polymorphisms of the regulatory region of the gene encoding the negative regulator CYP24A1 [18] have been associated with SLE: in subjects with increased genetic risk for SLE development, the presence of two copies of the minor allele is able to increase 25(OH)D3 levels reducing the risk of having the disease [50].…”
Section: Risk Factors For Vitamin D Deficiencymentioning
confidence: 99%